Acetylation‐Deacetylation‐Driven Natural Product Biosynthesis - Huibin Wang; Ikuro Abe (ChemistryEurope)
Abstract Acetylation introduces acetyl groups to substrates, thus altering their chemical reactivity and stability, and plays a crucial role in natural product biosynthesis by driving structural diversification and functional optimization. Emerging evidence now highlights cryptic acetylations as transient modifications that guide sequential reactions, enabling the efficient assembly of bioactive molecules. Here, we systematically examine the multifaceted roles of acetylation‐deacetylation dynamics in natural product biosynthesis, with particular emphasis on four key mechanistic paradigms. First, we explore the strategy of acetylation followed by deacetylation after several biosynthetic steps, which serves as a protective and directing mechanism. Second, we investigate acetylation‐mediated rearrangement, where the introduction of an acetyl group triggers structural rearrangement to generate novel molecular architectures. Third, we analyze acetylation‐triggered elimination, a process that facilitates the formation of crucial double bonds in molecular scaffolds. Finally, we discuss the acetylation cycle as a regulatory mechanism, highlighting its role in controlling biosynthetic flux and intermediate stability. We also examine the challenges of identifying and characterizing cryptic acetylations, while highlighting future opportunities to harness these modifications for synthetic biology. By elucidating the hidden roles of acetylation‐deacetylation dynamics, this not only deepens our understanding of natural product biosynthesis but also provides innovative strategies for future drug discovery.